Tradisi Ureh dalam Bercocok Tanam pada Masyarakat Desa Keude Krueng Sabee Kabupaten Aceh Jaya - Asyura; Abdul Manan; Ruhamah (The Department of Islamic History and Culture in cooperation with the Center for Research and Community Service, Universitas Islam Negeri Ar-Raniry Banda Aceh, Aceh, Indonesia, 2020)
This paper is entitled Ureh Tradition in Farming in Keude Krueng Sabee Village Community, Aceh Jaya Regency. This study focuses on the local wisdom tradition of the community in farming (rice plants). The purpose of this paper is to find out more about the history, implementation processions, and community responses. The type of research used is a qualitative approach with observation, interview and documentation techniques. Data were analyzed through descriptive qualitative approaches, and natural setting. The results showed that the ureh tradition is a community habit that they practice in the context of farming, and its implementation is individual. Ureh is a tradition of protecting plants from pests in the form of a mystical fence. The ureh tradition is practiced from the nursery to harvesting. There are two forms of implementation: (1); zimat with conditional objects, (2); its zimat only. The ureh tradition in the form of a mystical fence is rarely practiced by the community, and is considered irrelevant, except only in rural communities, but for people close to urban areas they use “modern” ureh which is considered more effective and efficient.